Pontobdella muricata and Trachelobdella lubrica (Hirudinea: Piscicolidae) on some marine fish in the Dardanelles, Turkey - Saglam, N; Oguz, MC; Celik, ES; Doyuk, SA; Usta, A (Cambridge Univ Press, 2003)
Fifteen individuals of four marine fish species (Torpedo marmorata, Raja clavata, Scorpaena porcus and Scorpaena scrofa) caught in the Dardanelles, Turkey, were examined for the leech Pontobdella muricata and Trachelobdella lubrica; 18 P. muricata and 23 T. lubrica were found on gills, at the base of the fins, and abdomen on 14 of the 15 fish.